2011
DOI: 10.2337/dc11-0098
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Detemir Reduces Weight Gain as a Result of Reduced Food Intake in Patients With Type 1 Diabetes

Abstract: OBJECTIVEInsulin detemir lacks the usual propensity for insulin to cause weight gain. We investigated whether this effect was a result of reduced energy intake and/or increased energy expenditure.RESEARCH DESIGN AND METHODSA 32-week, randomized crossover design trial was undertaken in 23 patients with type 1 diabetes. Patients on a basal-bolus regimen (with insulin aspart as the bolus insulin) were randomly assigned to insulin detemir or NPH insulin as a basal insulin for 16 weeks, followed by the other basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 24 publications
1
44
0
2
Order By: Relevance
“…In a randomized crossover study, it was found that the weight sparing effect of insulin detemir was due to reduced food intake rather than increased energy expenditure, possibly through direct or indirect effects of insulin detemir on the hormones that control satiety. 25 This concept is supported by the finding that insulin detemir activates the hypothalamus, 26 which centrally controls appetite and body weight. 27 There were certain limitations to the present study, including the small sample size and observational study design.…”
Section: Discussionmentioning
confidence: 95%
“…In a randomized crossover study, it was found that the weight sparing effect of insulin detemir was due to reduced food intake rather than increased energy expenditure, possibly through direct or indirect effects of insulin detemir on the hormones that control satiety. 25 This concept is supported by the finding that insulin detemir activates the hypothalamus, 26 which centrally controls appetite and body weight. 27 There were certain limitations to the present study, including the small sample size and observational study design.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, despite a limited study population and an open‐label design, the findings of Zachariah et al. 26 suggest that the weight‐sparing effect of insulin detemir can be attributed to reduced caloric intake. Moreover, the study further confirms that change in energy intake is not linked to hypoglycaemia.…”
Section: Food Intake Modelmentioning
confidence: 99%
“…This effect of insulin detemir (Levemir) on body weight may result from its effect on the brain, as well as the ability of the central nervous system to help regulate hunger and satiety, hypoglycemia risk reduction, greater hepatoselectivity, lower lipotropism and the ability to alleviate deficient incretin function via the increased secretion of GLP-1 [72][73][74][75]. The data obtained in the analysis of non-pregnant patients with DM suggest new additional opportunities in the treatment of patients experiencing difficulties in controlling weight gain during pregnancy.…”
Section: репродуктивное здоровьеmentioning
confidence: 99%